Using Cathodic Poised Potential Experiments to Investigate Extracellular Electron Transport in the Crustal Deep Biosphere of North Pond, Mid-Atlantic Ridge - Jones, Rose M.; D’Angelo, Timothy; Orcutt, Beth N. (Frontiers in Environmental Science, 2020)
The crustal sub-seafloor covers a large portion of the Earth’s surface but is poorly understood as a habitat for life. It is unclear what metabolisms support the microscopic cells that have been observed, and how they survive under resource limitation. As the deep crustal subsurface represents a significant portion of the Earth’s surface, microbially-mediated reactions may therefore be significant contributors to biogeochemical cycling. In the present study, we used electrochemical techniques to investigate the possibility that crustal subsurface microbial groups can use the solid rock matrix (basalts, etc.) as a source of electrons for redox reactions via extracellular electron transfer (EET). Subsurface crustal fluids and mineral colonization experiments from the cool and oxic basaltic crustal subsurface at the North Pond site on the western flank of the Mid-Atlantic Ridge were used as inocula in cathodic poised potential experiments. Electrodes in oxic microbial fuel cells were poised at -200 mV versus a standard hydrogen electrode to mimic the delivery of electrons in an energy range equivalent to iron oxidation. In this way, microbes that use reduced iron in solid minerals for energy were selected for from the general community onto the electrode surface for interrogation of extracellular electron transfer activity, and potential identification by scanning electron microscopy and DNA sequencing. The results document that there are cathodic EET-capable microbial groups in the low biomass crustal subsurface at this site. The patterns of current generation in the experiments indicate that these microbial groups are active but likely not growing under the low-resource condition of the experiments, consistent with other studies of activity versus growth in the deep biosphere. Lack of growth stymied attempts to determine the phylogeny of EET-capable microbial groups from this habitat, but the results indicate that these microbial groups are a small part of the overall crustal deep biosphere community. This first demonstration of using electromicrobiology techniques to investigate microbial metabolic potential in the crustal deep biosphere reveals the challenges and opportunities for studying EET in the crustal deep biosphere.